Alveolar Soft Part Sarcomas: Molecular Pathogenesis and Implications for Novel Targeted Therapies. (8th April 2012) - Mitton, Bryan; Federman, Noah
Abstract : Alveolar soft part sarcoma (ASPS) is a very rare soft tissue sarcoma which arises primarily in children and young adults. Despite its unique histology and well-characterized genetic translocation, many questions remain regarding the pathogenesis and treatment of this tumor type. Though collective clinical experience with this tumor type spans more than 60 years, there has been little progress made in treating this uncommon but frequently fatal disease. This paper focuses on the available data regarding its molecular pathogenesis and insights into targeted therapeutics as well as the results of clinical trials performed to date to hopefully improve the outcome of patients with this rare malignancy.